1988
DOI: 10.1248/cpb.36.4253
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of hemolytic action of lysophosphatidylcholines in vitro: Effect of acyl chain structure.

Abstract: Hemolysis of rabbit erythrocytesby several lysophosphatidylcholines(lysoPCs)containing C12-C18 saturated and cis unsaturated acyl chains was investigated in vitro.The degree of hemolysis was dependent on the erythrocyte concentration used.Based on this dependency,two determinants for the drugs'hemolytic activity,namely,their affinity for the cell membrane and their intrinsic hemolytic activity,were analyzed separately to clarify the relationship between these factors and the acyl chain structure.Elongation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The final concentration was 50 mM. The critical micelle concentration of oleoyl lyso-PC is 2 mM in phosphate-buffered saline (28). The micelles were incubated for 1 h at 23 C before size measurement.…”
Section: Size Determination Of Extruded Unilamellar Vesiclesmentioning
confidence: 99%
“…The final concentration was 50 mM. The critical micelle concentration of oleoyl lyso-PC is 2 mM in phosphate-buffered saline (28). The micelles were incubated for 1 h at 23 C before size measurement.…”
Section: Size Determination Of Extruded Unilamellar Vesiclesmentioning
confidence: 99%
“…The proportion of the hydrophilic group to the hydrophobic group in LPC is greater than that in PC, and the ability of the emulsification of LPC is characteristically great. LPC also, however, causes hemolysis because LPC has not only the ability of emulsification but also very high solubility, and thus a fat emulsion using LPC as the emulsifier cannot be used for parenteral emulsions [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Quinn et al [17] have shown LPC to be a potent and specific chemoattractant for monocytes. This substance is cytotoxic to various cells, including myocardial cells [18], lymphocytes [19], erythrocytes [20], alveolar epithelial cells [21], and human lymphoma Raji cells [22].…”
Section: Discussionmentioning
confidence: 99%